Faktor-Faktor Yang Mempengaruhi Kepuasan Nasabah PT BPR Bank Bapas 69 Pengguna Mobil Kas Keliling di Kabupaten Magelang - Novi Erawati; Ivo Novitaningtyas (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2022)
The purpose of this study was to determine the effect of service quality, security, and mobile cash car facilities at PT BPR Bank Fathers 69 on the level of customer satisfaction. This research uses descriptive quantitative method. The population of the research is the customers of PT BPR Bank Fathers 69 who use the mobile case car facility, and the sample used is 100 respondents. The primary data that has been collected is then processed using SPSS 20. The results show that there is an influence of service quality, security, and mobile cash car facilities on customer satisfaction as much as 63.7% while the remaining 36.3% is influenced by other variables. In addition, the variables of service quality, security, and facilities have been shown to have a partial and simultaneous effect on customer satisfaction.